The Impact of Using Listening Triangle Strategy on Iraqi College Student’s Achievement in Language Assessment Courses (Journal of Imam Al-Kadhim College, 2024)
Objectives: The present study examines the efficacy of using the Listening Triangle Strategy (LTS) to increase the knowledge acquisition and comprehension of Iraqi college students who are studying English, which is an assessment-based course.Method: A quasi-experiment was conducted to achieve the goals of the present study. The veracity of its results was determined using T scores. The participants were fourth-year English language students at the Imam Al-Kadhum College in the 2023-2024 academic year. Sixty students were selected and randomly divided into two groups. Group A, the experimental group with 30 students, used the LTS for their studies, while Group B, also with 30 students, served as the control group and followed traditional learning methods. To meet the study's goals, researchers developed a 10-item multiple-choice test on assessment topics, ensuring its validity and reliability.Results: The results of the post-test revealed that Group A (277) scored significantly higher than Group B (25.2). This difference was statistically significant. Therefore, the proposed null hypothesis was unsupported, while the alternate hypothesis was supported. Therefore, the LTS can help students improve their listening and speaking skills which, in turn, increases their comprehension of assessment-based topics.Conclusion: The research showed that it is crucial to teach evaluation subjects through the LTS, and additional courses need to focus on implementing this method in public schooling.
Keywords: The Listening Triangle, Strategy, Language Assessment, Achievement